Efektivitas Terapi Aktivitas Kelompok Berbasis Mindfulness dalam Mengurangi Gejala Halusinasi pada Pasien Skizofrenia dI RSUD Madani: Penelitian - Sri Indri; Ahmil Kiding; Sintong H. Hutabarat (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Background: Schizophrenia is a chronic mental disorder characterized by disturbances in perception, including hallucinations, which may impair social functioning and increase the risk of harm to oneself or others. One effective non-pharmacological intervention is mindfulness-based Group Activity Therapy (GAT). Objective: This study aimed to analyze the effectiveness of mindfulness-based GAT in reducing hallucination symptoms among patients with schizophrenia at Madani Regional Hospital, Palu City. Methods: A quantitative pre-experimental study with a one-group pretest–posttest design was conducted involving 15 patients selected through purposive sampling. The intervention consisted of four sessions of mindfulness-based GAT. Hallucination symptoms were assessed using a hallucination observation checklist, and data were analyzed using a paired t-test. Results: The mean hallucination symptom score decreased from 33.27 ± 2.12 before the intervention to 30.80 ± 1.56 afterward. The paired t-test showed a significant difference (p = 0.000; p < 0.05). Conclusion: Mindfulness-based GAT was effective in reducing hallucination symptoms and can be recommended as a non-pharmacological nursing intervention for patients with schizophrenia.